Subcutaneous Immunization with Fusion Protein DnaJ-ΔA146Ply without Additional Adjuvants Induces both Humoral and Cellular Immunity against Pneumococcal Infection Partially Depending on TLR4 - Su, Yufeng; Li, Dagen; Xing, Yan; Wang, Hong; Wang, Jian; Yuan, Jun; Wang, Xiaofang; Cui, Fang; Yin, Yibing; Zhang, Xuemei (Frontiers in Immunology, 2017)
Subunit vaccines that are poorly immunogenic are often combined with adjuvants for immunization. Our previous research identified a pneumolysin variant (∆A146Ply), a Toll - like receptor 4 agonist, that was an effective adjuvant in the protection of fusion protein DnaJ-∆A146Ply against mucosal Streptococcus pneumoniae infections. For pneumcoccal vaccines, World Health Organization recommend injection as a regular vaccination approach. Subcutaneous immunization is a common and effective method of injection, so we explored the immunity mechanism of subcutaneous immunization with DnaJ- ∆A146Ply. We found that mice immunized subcutaneously with fusion proteins ∆A146Ply-DnaJ and DnaJ-∆A146Ply produced a higher anti-DnaJ IgG titer than when DnaJ alone was administered. DnaJ-∆A146Ply induced both B-cell and T-cell-dependent protection against both colonization and lethal pneumococcal infections. Levels of IFN-γ, IL-4 and IL-17A were also elevated in DnaJ-∆A146Ply immunized mice. However, all these effects were negated in TLR4-/- mice compared to WT mice immunized with DnaJ-∆A146Ply. B-cell-deficient μMT mice, nude mice, IFN-γ-/- and IL-4-/- mice immunized with DnaJ-∆A146Ply could not resist infection with pneumococci. IL-17A-/- and TLR4-/- mice did not benefit from DnaJ-∆Ply immunization in colonization experiments although their survival was not impaired compared with WT mice. Collectively, our data indicated that ∆A146Ply can be a potential subcutaneous adjuvant, and the DnaJ-∆A146Ply fusion protein induces both humoral and cellular immune response to resist S. pneumoniae infection. The protective effect of colonization also depends on TLR4.